Pengaruh Likuiditas, Solvabilitas Dan Profitabilitas Terhadap Harga Saham Perusahaan Indeks Lq 45 Tahun 2014 – 2018 - Tatang Kosasih; Elfreda Aplonia Lau; Imam Nazarudin Latif (Journal of Indonesian Science Economic Research, 2019)
This study aims to analyze the influence of Likuidity seen from Current Ratio, Solvability seen from Debt to Equity Ratio dan Profitability seen from Return On Asset to Share Price of Index LQ 45 Companies in Indonesia Stock Exchange (BEI) in 2014 – 2018.The population in this study are the companies index LQ 45 that are included in the Indonesia Stock Exchange (BEI) in 2014 – 2018. Sample selection is taken by using purposive sampling method. The number of samples are 15 index LQ 45 in Indonesia Stock Exchange (BEI). Data which is secondary data. The classical principle test used in this study is by using normality test, multicolerity test, heteroxidity test, and autocorrelation test. The analysis used in this research is multiple regression method.Based on the calculation results show that the Current Ratio is not significant to Share Price index LQ 45 in Indonesia Stock Exchange (BEI). Debt to Equity Ratio is not significant to Share Price index LQ 45 in Indonesia Stock Exchange (BEI). Return On Asset is significant to Share Price index LQ 45 in Indonesia Stock Exchange (BEI). Current Ratio, Debt to Equity Ratio, dan Return On Asset is not significant to Share Price index LQ 45 in Indonesia Stock Exchange (BEI).